Syntactic change in Anglo-Norman and continental French chronicles: was there a ‘Middle’ Anglo-Norman? - INGHAM, RICHARD (Journal of French language studies, 2006)
Anglo-Norman (AN) showed a tendency to lose Old French conjugation and gender inflectional distinctions, but is thought to have largely maintained the syntax of Old French. This study considers whether in the early 14th century AN syntax continued to follow continental French (CF) by moving towards new word-order patterns, namely XSV order and subject-verb inversion after et, which were to typify Middle French. Using corpora of CF and AN historical writing, especially chronicles, it is found that AN to some extent shadowed developments found in later 13th and in 14th century CF. In both AN and CF, XSV order was widespread with time adjuncts, but avoided with place adjuncts and direct and indirect objects. This dissociation was not calqued on Old/Middle English subject-verb inversion, which showed a different dissociation, i.e. inversion of verb and nominal subjects, but not pronominal subjects; AN showed no influence of this contrast. Inversion after et was found in AN, but only with unaccusative verbs, whereas in CF by the late 13th century it was spreading to other verbs as well, having initially shown a similar limitation as in AN. It is concluded that underlying syntactic processes of change began to affect AN as well as CF, but that they were interrupted by the switch away from French in England in the later 14th century.